Phytopathogen resistance of phytohormone-deficient and low-sensitivity mutant tomatoes - Dias Tunes, Carla; Pinto Gonçalves, Vanessa; Brandstetter Rodrigues, Daniele; da Silva Almeida, Andréia; Rossatto Meneses, Priscila; Milech Neumann, Alexandre (Revista Ceres, 2025)
This study broadens the knowledge of plant-pathogen interactions using phytohormone-deficient and low-sensitivity mutant tomatoes. The experiment was performed under greenhouse conditions and the mutants used were provided by the HCPD laboratory, at ESALQ/USP. The hormone mutant Never ripe showed a larger final lesion size when inoculated with Botrytis cinerea, whereas curl3 was relatively resistant to this pathogen and more susceptible when inoculated with Phytophthora infestans. The transgenic 35S :: nahG was more susceptible to Oidium lycopersici, and the double mutant dgt, Nr more resistant. The low sensitivity to brassinosteroids confers greater susceptibility to P. infestans and higher resistance to B. cinerea. The deficiency of the hormone auxin promotes high resistance to diseases caused by O. lycopersici, P. infestans and B. cinerea.